Sickness absence trajectories among young employees in their first full-time employment and subsequent long-term sickness absence: a Danish register-based cohort study - Naja Hulvej Rod; Tea Lallukka; Ida Madsen; Ute Bültmann; Maria Melchior; Reiner Rugulies; Jacob Pedersen; Stephen Stansfeld; Jeppe Karl Sørensen; Karl Bang Christensen; Jimmi Mathisen (BMJ Public Health)
Background Sickness absence (SA) poses an important and costly societal and public health challenge. However, no previous studies have investigated SA trajectories among individuals in their first full-time employment, delving into the contribution of early SA to future long-term absence among young employees. We aimed to identify SA trajectories in young full-time employees and explore them as risk markers for subsequent long-term SA (LTSA).Method In a nationwide register-based cohort of 91 633 young employees (aged 15–30) entering the Danish labour market between 2010 and 2018, we applied group-based multi-trajectory modelling to identify SA trajectories based on daily information on SA during the first year of full-time employment. Proportional hazard models were used to examine associations between trajectory groups and subsequent 2-year risk of LTSA after the first year (>30 days).Results A model with three distinct SA trajectory groups was selected: (1) no or few shorter SA spells (59% for women, 62% for men), (2) frequent shorter spells (36% for women, 34% for men) and (3) frequent longer spells (6% for women, 4% for men). A clear social and health gradient in SA trajectories was identified with individuals with frequent shorter or frequent longer SA spells having lower education and a history of mental health problems. Compared to having no or few shorter spells, belonging to trajectories with frequent shorter or longer spells was associated with higher risk of subsequent LTSA (fully adjusted HRs ranging from 1.82 to 2.21).Conclusion Around 40% of young employees’ SA was characterised by frequent shorter or longer spells during the first year of full-time employment, constituting an early risk marker for future LTSA. More attention should be paid to young individuals who, at the beginning of their work life, show increased SA patterns.